Physicochemical characterization of 'Golden' pitaya pulp and bark (Research, Society and Development, 2021)
The objective of this work was to evaluate the physicochemical characteristics of the pulp and bark of pitaya 'Golden'. The experimental design consisted of a unifactorial scheme, with two levels (pulp and peel), using ten replications of one fruit each. The physicochemical characteristics mentioned below were evaluated. For soluble solids and pH, pulp and skin had mean values of 8,31 and 4,50 ºbrix and 4,79 and 5,02 respectively. Regarding the titratable acidity, the peel and pulp had averages of 0,34% and 0,18% of malic acid. For the average fruit mass, pulp and skin mass, average values of 360,45g, 264,04g and 95,63g were obtained, respectively. Regarding the variables fruit length, pulp length, fruit diameter and pulp diameter, it was observed 138,65mm, 98,67mm, 73,58mm and 63,78mm, respectively. As for peel and pulp firmness, the average value was 9,38 N and 5,89 N, respectively. In the thickness of the shell, there was an average of 2,98 mm. As for luminosity and hue angle, mean values of 61,68 and 81,79 were observed for peel and pulp, respectively. As for the pulp, the average values were 35,04 for variable brightness and 83,36 for the hue angle. It was concluded that the pulp and bark of pitaya 'Golden' have physicochemical characteristics according to the literature, having potential both for fresh consumption and for industrial use, as well as adequate size proportions for the foreign market.